2016
DOI: 10.1007/s00339-016-0293-3
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction line profile analysis of KBr thin films

Abstract: In the present work, the microcrystalline characteristics of KBr thin films have been investigated by evaluating the breadth of diffraction peak. The Williamson-Hall, the Size-Strain Plot and the single line Voigt methods are employed to deconvolute the finite crystallite size and microstrain contribution from the broaden X-ray profile. The texture coefficient and dislocation density have been determined along each diffraction peak. Other relevant physical parameters such as stress, Young's modulus and energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 39 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…This increment in photocurrent is related to the ejection of more photoelectron from photocathode surface with increasing thickness. From X-ray diffraction analysis of these films, which we have reported in our earlier article [26], it was found that defect density as well as microstrain decrease and therefore, film crystallinity improves with increasing thickness. The film with a better crystal structure and fewer impurities, ejected electrons will have a higher probability of survival through transport towards vacuum interface and contribute to the photocurrent.…”
Section: Photoemission Studiesmentioning
confidence: 64%
“…This increment in photocurrent is related to the ejection of more photoelectron from photocathode surface with increasing thickness. From X-ray diffraction analysis of these films, which we have reported in our earlier article [26], it was found that defect density as well as microstrain decrease and therefore, film crystallinity improves with increasing thickness. The film with a better crystal structure and fewer impurities, ejected electrons will have a higher probability of survival through transport towards vacuum interface and contribute to the photocurrent.…”
Section: Photoemission Studiesmentioning
confidence: 64%
“…Spectral fitting of X-ray diffraction (XRD) patterns. As (200) and its harmonic (400) presented the same atomic distributions, it is rational to discuss the representative face of (400) for the face analysis and the interaction energy calculation [47,48]. On (400), regular distributions of calcium, oxygen, and hydrogen atoms indicated the similar adsorption of the calcium oleate and SDBS due to the similar carbon chain length and functional group.…”
Section: Analysis Of the Crystal Facesmentioning
confidence: 93%
“…The deviation from the crystallinity is ascribed to the presence of lattice distortion owing to the limited crystallite size and the microstrain. 44 The XRD patterns presented in Fig. 2 show the diffraction peaks for the He-Ne laser irradiated Sn 0.04 Co 0.06 O 2 thin films (22 mW) with different exposure times of 0, 1, 2, 15, 40, and 60 min.…”
Section: Microstructural Analysismentioning
confidence: 99%